A New Class of Extended Tetrathiafulvalene Cruciform Molecules for Molecular Electronics with Dithiafulvene‐4, 5‐Dithiolate Anchoring Groups. (20th August 2012) - Parker, Christian Richard; Wei, Zhongming; Arroyo, Carlos R.; Jennum, Karsten; Li, Tao; Santella, Marco; Bovet, Nicolas; Zhao, Guangyao; Hu, Wenping; van der Zant, Herre S. J.; Vanin, Marco; Solomon, Gemma C.; et al.
<x xml:space="preserve">Abstract</x> Cruciform motifs with two orthogonally oriented π‐extended tetrathiafulvalenes and with differently protected thiolate end‐groups are synthesized by stepwise coupling reactions. The molecules are subjected to single‐molecule conductivity studies in a break‐junction and to conducting probe atomic force microscopy studies in a self‐assembled monolayer on gold. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>